2010
DOI: 10.1177/0973258612471245
|View full text |Cite
|
Sign up to set email alerts
|

High Film Centricity in Indian Television Channels

Abstract: A first-ever study of the content-programmes and their formats-of regional television (TV) channels of the largest south Indian state, Andhra Pradesh, working on a 24x7 pattern, has revealed the progressive decadence of public sphere and growing trivialization. The contents were singularly dependent on films and film-related materials such as songs, comedy clippings of scenes and dances for majority of their programmes, and contents as well. Grounded in the observation method (Rao 2008), the study is a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Though India has about 15 big media conglomerates, 900 television channels and 150 FM radio stations, the public sphere is highly contracted and immature. Most of the media are dominated by content related to film (stardom, star profiles, box-office performances, latest film audio releases, teaser, poster releases, film programs, film telecasting, film clippings, etc), celebrity, crime and cricket (Murthy, 2010). In his study of Telugu television phenomenon in the then State of Andhra Pradesh (which has 57 television channels, the highest in any federal State in India), Murthy (2010) has observed that Telugu television seemed to exhibit a unique pattern of performance, described as a 'butterfly metamorphosis' dictated by third world market compulsions, that cannot be interpreted by any of the existing the International Communication Gazette 78( 7) media theories on the television content in the West (p. 170).…”
Section: Indian/asian Communication Research: a Developing Alternative Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Though India has about 15 big media conglomerates, 900 television channels and 150 FM radio stations, the public sphere is highly contracted and immature. Most of the media are dominated by content related to film (stardom, star profiles, box-office performances, latest film audio releases, teaser, poster releases, film programs, film telecasting, film clippings, etc), celebrity, crime and cricket (Murthy, 2010). In his study of Telugu television phenomenon in the then State of Andhra Pradesh (which has 57 television channels, the highest in any federal State in India), Murthy (2010) has observed that Telugu television seemed to exhibit a unique pattern of performance, described as a 'butterfly metamorphosis' dictated by third world market compulsions, that cannot be interpreted by any of the existing the International Communication Gazette 78( 7) media theories on the television content in the West (p. 170).…”
Section: Indian/asian Communication Research: a Developing Alternative Paradigmmentioning
confidence: 99%
“…Most of the media are dominated by content related to film (stardom, star profiles, box-office performances, latest film audio releases, teaser, poster releases, film programs, film telecasting, film clippings, etc), celebrity, crime and cricket (Murthy, 2010). In his study of Telugu television phenomenon in the then State of Andhra Pradesh (which has 57 television channels, the highest in any federal State in India), Murthy (2010) has observed that Telugu television seemed to exhibit a unique pattern of performance, described as a 'butterfly metamorphosis' dictated by third world market compulsions, that cannot be interpreted by any of the existing the International Communication Gazette 78( 7) media theories on the television content in the West (p. 170). He has arrived at this finding after testing the relevance of a host of 'effects theories' ranging from magic bullet theory to uses and gratification theory through different layers of social theories such as hegemony theory, critical theory, neo-liberal theory, social integrative action theory, etc.…”
Section: Indian/asian Communication Research: a Developing Alternative Paradigmmentioning
confidence: 99%
“…Similar research is needed in television, advertising, and public relations for the terms of Indian democracy and its working in relation to the above media institutions is not exactly the same as that of the US or UK (read Nair 2012). In so far as technology is concerned, there might be technological semblances between the West and India, but the rest of the phenomena, both social and media, are not the same as that of the West (Murthy 2010b). Therefore, the contention that Western theories can fully explain Indian media and social phenomena is quite untenable.…”
Section: Pedagogic and Curricular Modules For Indian Mass Communicationmentioning
confidence: 99%